Victor Orindi, Kenya: National Adaptation Plans and Agriculture learning workshop 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
A 2-day workshop hosted by the CGIAR Research Program on Climate Change, Agriculture and Food Security from 13-14 November, Warsaw, Poland, brought together 37 representatives from 10 different countries across Asia, Africa and Latin America to share their lessons and experiences in developing climate adaptation plans for the agriculture sector. Here, Victor Orindi shares his hopes for the key messages he will bring back with him to Kenya. For more information see: "Planning climate adaptation in agriculture" http://ow.ly/qSN00 "New reports highlights lessons from national adaptation planning" http://ow.ly/qSN1h